2006
DOI: 10.1021/la060134b
|View full text |Cite
|
Sign up to set email alerts
|

Domain Memory of Mixed Polymer Brushes

Abstract: The nano-phase-separation in mixed polymer brushes consisting of polystyrene and poly(methyl methacrylate) (PS-PMMA) chains attached to a silicon surface is studied. The topographies of the mixed brushes are examined after they have been exposed to solvents which induce or erase nano-phase-separation. It is discussed whether the brush locally forms the same pattern every time the transition from the smooth and featureless to the nanopatterned state occurs ("domain memory") or if the local assembly of the domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
58
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 22 publications
(61 reference statements)
1
58
0
Order By: Relevance
“…4) (Movie S2 in Supporting Information). [31] For the system shown here, the maximum length of one step was 200 nm (the third cycle in Fig. 4); the average length of one step made by the sphere was 100 nm.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…4) (Movie S2 in Supporting Information). [31] For the system shown here, the maximum length of one step was 200 nm (the third cycle in Fig. 4); the average length of one step made by the sphere was 100 nm.…”
mentioning
confidence: 85%
“…For the particular brush described above, a certain area on the brush was selected and its topography was acquired after each cycle of acetone/toluene exposure. [31] When comparing single domains over several switching cycles, it was found that some recover almost completely with only a slight variation in shape, but others turn into a dissimilar pattern (Fig. 3).…”
mentioning
confidence: 97%
See 3 more Smart Citations